Chlormethine gel in combination with other therapies for treatment of mycosis fungoides: a review with patient cases - Ardigò, Marco; Nikbakht, Neda; Teoli, Miriam; Gleason, Laura; Crisan, Liliana; Querfeld, Christiane (Frontiers in Medicine, 2024)
Topical chlormethine gel has been approved as monotherapy for treatment of adult patients with mycosis fungoides (MF), the most common form of cutaneous T-cell lymphoma. In clinical practice, chlormethine gel is often combined with other skin-directed or systemic therapies to optimize response and target recalcitrant lesions. Positive outcomes with combination regimens using chlormethine gel and topical corticosteroids, phototherapy, retinoids, methotrexate, or interferon-α have been reported in literature. However, there are no treatment guidelines on the use of combination regimens with chlormethine gel. To provide real-world evidence and guidance on the use of chlormethine gel combination regimens, several cases of patients treated with chlormethine gel combined with phototherapy (n = 5), retinoids (n = 16), or mogamulizumab (n = 3) are presented. These different combination regimens showed promising results. Most patients had a complete or partial response following treatment and the combinations were well-tolerated over extended treatment periods. Patients receiving chlormethine gel with retinoids had long-term periods of remission, even after treatment discontinuation. Durations of response of up to 3 years were observed in these patients. This long-term disease control may be the result of disease-modifying effects of chlormethine. Previous studies have shown targeted reductions in malignant T-cell clones in patients treated with chlormethine gel as well as improved post-treatment responses. Further research is needed to determine the effectiveness and safety of combination treatment regimens with chlormethine gel and to assess the impact chlormethine gel has on disease control.